2010
DOI: 10.4103/0255-0857.62484
|View full text |Cite
|
Sign up to set email alerts
|

Dengue NS1 antigen detection: A useful tool in early diagnosis of dengue virus infection

Abstract: NS1 Ag assay holds promise in early diagnosis of dengue infection. When used in combination with MAC-ELISA on a single sample it significantly improves the diagnostic algorithm without the requirement of paired sera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 10 publications
(11 reference statements)
9
56
0
5
Order By: Relevance
“…Similar male preponderance was observed by various authors in previously reported outbreaks [11,12]. Srivastav et al, reported only 26% NS1Ag positivity but Dutta and Wattal had reported higher percentage of NS1Ag positivity (71.42%) in acute phase sera [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…Similar male preponderance was observed by various authors in previously reported outbreaks [11,12]. Srivastav et al, reported only 26% NS1Ag positivity but Dutta and Wattal had reported higher percentage of NS1Ag positivity (71.42%) in acute phase sera [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…This is the reason for its high detection rate in acute phase sera. [18] In this study, only NS1 antigen was positive in 57.95% of the cases [ Fig. 2].…”
Section: Seroepidemiology and Gender Related Differences In Laboratormentioning
confidence: 63%
“…In rest of 32 positive cases both NS 1 antigen and Ig M antibody were detected. Various studies have indicated that NS 1 antigen helps in early detection and confirmation of diagnosis (Kulkarni et al, 2011;Datta et al, 2010;Krunal Mehta et al, 2016). When month wise trend was depicted on graph it reinforced the fact that surge in Dengue vector and so the rise in dengue cases occur in Monsoon and post monsoon season (WHO Dengue fever 2nd Edition 1997, Madhulika Mistry et al, 2015;Durani et al, 2014;Piyush tripathi et al, 2008 …”
Section: Resultsmentioning
confidence: 99%